Spiritual Emotional Freedom Technique with Quality of life and Depression in HIV/AIDS Patients: Systematic Review - Firmansyah, Doddy; Gultom, Satriani; Dame, Artha Marisi; Suherlan, Herlan; Ernawati, Dedeh; Manurung, Sarida Surya; Kamil, Abdu Rahim (Universitas STRADA Indonesia, 2021)
Background: Quality of life and depression in HIV patients is an impact that will be received by HIV patients if the intervention is not carried out properly, to reduce the impact that will occur to eliminate the worst impacts, HIV patients must always be motivated and approach in the form of counseling and other approaches such as spiritual emotional freedom technique.Purpose: The purpose of this study was to collect the right type of therapy or intervention to reduce depression rates due to psychological impacts on HIV patients and improve the quality of life of HIV patients.Methods: The design of this study uses a systematic review approach by collecting several articles from a selected database consisting of science direct, pubmed and proquest with articles published in 2016-2021. The search for articles was conducted by entering the words